Effects Of Combined Nutrient And Water Stress On The Growth Of Hopea Odorata Roxb. And Mimusops Elengi Linn. Seedlings - Zainudin, S.R; Awang, Kamis; Mohd. Hanif, Ahmad Husni (Taylor & Francis, 2003)
The growth of Hopea odorata and Mimusops eiengi seedlings under drought and various fertilization rates under nursery conditions was investigated. Both H. odorata and M. e1engi seedlings responded differently to fertilizer application and drought Application of slow-release fertilizer (Best Tab, 20: 10: 5 NPK) at 30 and 50 g promoted greater growth for H. odorata and M eiengj·seedlings. respectively. M eif'llgi seedlings were able to tolerate high fertilizer application (50 g), but the resulting form (small trunk diameter and excessive height) was not suitable for urban planting. Growth of H. odorata seedlings was greatly promoted through application of 30 g of fertilizer under wellwatered conditions, resulting in a much more balanced growth in terms of shoot and root ratio, which is vital for plants growing in the harsh urban environment where competition for water and nutrients is usually intense.